Assessment Of The Place And Role Of Personnel ManagementIn The General Management System Of The Organization - Kovalenko, Yelena; Коваленко, Олена; Kirdan, Oleksandr; Кирдан, Олександр; Krivonos, Anatoliy; Крівонос, Анатолій; Dobrovolska, Olena; Добровольська, Олена Володимирівна; Gutsul, Tetiana; Гуцул, Тетяна; Hromov, Sergii; Громов, Сергій (International Journal of Computer Science and Network Security (South Korea),IJCSNS, 2021)
The article assesses the role of the human factor in management, analyzes the personnel policy, as well as the style and methods of management at the enterprise. The purpose of the article is to study the place and role of personnel management in the general management system of an organization. Particular tasks of the research have been solved: the place and role of personnel management in the system of general management theory have been determined; determined the place of personnel management in the system of modern sciences. У статті оцінюється роль людського фактора в управлінні, аналізується кадрова політика, а також стиль і методи управління на підприємстві. Метою статті є вивчення місця і ролі управління персоналом в загальній системі управління організацією. Вирішені конкретні завдання дослідження: визначено місце і роль управління персоналом в системі загальної теорії управління ; визначено місце управління персоналом у системі сучасних наук.
Оцінка місця і ролі управління персоналом в загальній системі управління організацією
Keywords: management; управління; management system; система управління; organization; організація; general management; загальне управління